(untitled) (Transport systems and technologies, 2019)
The relevance of optimization and the quality of Ukrzaliznytsia’s activities based on the design-programming of infrastructure and argumentation of the rolling stock concept is substantiated and outlined. Ukrzaliznytsia as a large-scale complex and a system object from the point of view of the design of activities is a typical object, that should be developed by the methods of design programming. Ukrzaliznytsia has a complex multi-vector infrastructure, the optimality of which depends on the quality, competitiveness, as well as the identity and rationality of each component ’s style of activity of this infrastructure.The components, summarized with a methodological purpose, form the infrastructure of the Ukrzaliznytsia, namely: information support system; the subject environment, that is, the entire infrastructure of the railways; rolling stock; system of operation and services; personnel and passengers. Each of the individual components of the Ukrzaliznytsia’s infrastructure, including both characterized by substantive content, and substantively functional, as well as its place in the system of semantic relations of each component between each other within the framework of an integral system object - Ukrzaliznytsya. Expanding knowledge on each component, identifying problematic issues will make it possible to further generalize problems and move on to formulating targeted programs. As part of the target program or independently, the Design Program "Ukrzaliznytsya" can be developed and implemented.Keywords: design, method, design programming, concept, railway, optimization.